Pengaruh Iklan Tiktok terhadap Minat Beli Produk Skincare di SMK Perwira Negara - Zahira Zahira; Vivi Harmanda; Siska Miga Dewi (Jurnal Kajian dan Penelitian Umum, 2024)
This study examines the influence of TikTok advertisements on the purchasing interest in skincare products among female students at SMK Perwira Negara. With the increasing use of social media, TikTok has become an effective marketing platform. The aim of this research is to understand how advertisements affect skincare purchasing decisions and the challenges faced by students regarding product knowledge. The methodology used is a survey with a quantitative approach, where the population consists of female students who use skincare products. The sample was taken using purposive sampling, with a questionnaire as the data collection instrument. Data analysis was conducted statistically to test the hypothesis regarding the influence of TikTok advertisements. The results show that TikTok advertisements have a significant impact on the purchasing interest in skincare products. Influencers and creative content on TikTok can capture students' attention and alter their perceptions of the products. These findings emphasize the importance of marketing strategies through social media, where attractive and informative advertisements can enhance the desire to purchase. This research recommends that companies optimally utilize digital platforms to reach young consumers, considering the significant role of social media in current marketing.